2015
DOI: 10.1177/0333102415610873
|View full text |Cite
|
Sign up to set email alerts
|

Lateral inhibition in the somatosensory cortex during and between migraine without aura attacks: Correlations with thalamocortical activity and clinical features

Abstract: We hypothesize that abnormal migraine cycle-dependent dynamics of connectivity between subcortical and cortical excitation/inhibition networks may contribute to clinical features of MO and recurrence of attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 35 publications
10
58
0
Order By: Relevance
“…This findings is consistent with previous evidence obtained with psychophysiological tests [24], neuroimaging techniques [25, 26], and cortical EPs [46] showing that during the variable pain-free period between two migraine attacks, the brain of an individual with migraine is exposed to subtle cyclic functional changes. Indeed, at the cortical level, we previously observed that patients with MO and a subgroup of patients with migraine with visual aura associated with paraesthesia and/or dysphasia exhibited a strong decrease in EP amplitude habituation during the stereotyped presentation of visual stimuli with the passing of time from the last attack [4, 5].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This findings is consistent with previous evidence obtained with psychophysiological tests [24], neuroimaging techniques [25, 26], and cortical EPs [46] showing that during the variable pain-free period between two migraine attacks, the brain of an individual with migraine is exposed to subtle cyclic functional changes. Indeed, at the cortical level, we previously observed that patients with MO and a subgroup of patients with migraine with visual aura associated with paraesthesia and/or dysphasia exhibited a strong decrease in EP amplitude habituation during the stereotyped presentation of visual stimuli with the passing of time from the last attack [4, 5].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the abovementioned changes in EP according to the time elapsed from the last attack [4, 6], we hypothesised that motor cortex excitability would also become increasingly abnormal in patients with migraine as the time from the last migraine attack increased.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The thalamus was found to be implicated in many clinical [5861] and neurophysiological features of migraine [6264]. From animal experiments, it is known that the vast system of extrastriate and suprasylvian areas comprising the brain’s most important networks receive extensive projections from the lateral posterior-pulvinar thalamic complex, including the intralaminar nuclei [65, 66], that were recently reported to be reduced in volume in migraine patients scanned when attack-free [10].…”
Section: Discussionmentioning
confidence: 99%
“…Such a hypofunction may contribute to hyper-responsivity to external stimuli (Coppola et al , 2007), thus rendering the cortex more sensitive to external stimuli, and less capable of adapting to homeostatic changes. This may predispose to a migraine attack (Coppola et al , 2016).…”
Section: Discussionmentioning
confidence: 99%